PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI MEDIA KARTU ANGKA PADA ANAK USIA 4-5 TAHUN - Mortisari, Yuni; Syukri, M.; Amalia, Annisa (Universitas Tanjungpura, 2023)
The purpose of this study is to investigate the improvement in number concept recognition ability using number cards in 4-5 year old children in kindergarten. In this study, the action method was used. This form of study is a collaborative study of classroom activities.The subjects of the study were one teacher and 15 children aged 4 to 5 years.The data collection methods of this study are observation, interview, and documentation. This study was conducted in two cycles, each cycle consisted of two meetings, and each cycle consisted of four stages: planning, execution, observation, and reflection. The results of this study indicate that learning to recognize the concept of numbers through the media of number cards in children aged 4-5 years at Kindergarten has increased. According to the results of the study, the child's ability to recognize the symbols of the numbers 1 to 10 increased with each cycle. According to the data of this study, the child's number concept recognition ability using number card carriers increased by 18.2% in cycle 1 and cycle 2, while meeting 2 out of 33% in cycle 1 and cycle 2. It increased by 3% per period. This shows that 4-5 year old children in kindergarten can develop their. The ability to recognize the concept of numbers through playing number cards.